1972
DOI: 10.1128/jb.109.2.659-667.1972
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Secondary Metabolite Biosynthesis: Catabolite Repression of Phenoxazinone Synthase and Actinomycin Formation by Glucose

Abstract: Synthesis of the secondary metabolite, actinomycin, and the enzyme, phenoxazinone synthase, involved in the biosynthesis of the antibiotic, were shown to be under severe catabolite repression by glucose. Of a variety of hexoses and carbon compounds examined, glucose, and to a lesser extent, mannose, proved to be the most repressive for enzyme synthesis. The repression by glucose was most evident before production of the antibiotic. In a chemically defined medium suitable for actinomycin production, synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(29 citation statements)
references
References 24 publications
(24 reference statements)
2
27
0
Order By: Relevance
“…Actinomycin synthesis in S. antibioticus has been reported to be triggered through exhaustion of glucose during cultivation and that it was repressible by addition of glucose . Thus, to compare actinomycin formation (and peptide synthetase formation) in cultures of S. chrysomallus and S. antibioticus both strains were grown in a chemically defined medium containing glucose.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actinomycin synthesis in S. antibioticus has been reported to be triggered through exhaustion of glucose during cultivation and that it was repressible by addition of glucose . Thus, to compare actinomycin formation (and peptide synthetase formation) in cultures of S. chrysomallus and S. antibioticus both strains were grown in a chemically defined medium containing glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work indicated that actinomycin synthesis in S. antibioticus was repressible by glucose, and that the onset of its formation in glucose‐containing cultures was with glucose exhaustion in the later stages of cultivation . Moreover, other work indicated that formation of AcmA in S. antibioticus was repressible by glucose, too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RUPA-08PR which was found to produce high levels of antimicrobial metabolites in the medium supplemented with glucose (2%) as sole carbon source (Ripa et al, 2009). Higher glucose concentration has been reported to repress the formation of phenoxazinone synthetase, an enzyme required for producing antibiotic compound namely actinomycin synthesis (Gallo and Katz 1972) and higher glucose concentration will effect to metabolite repression, and production of secondary metabolite will decrease significant (Sunaryanto 2012).…”
Section: Screening Of Important Factors By Plackett-burman Designmentioning
confidence: 99%
“…Similar observation was reported by Syed et al [39] that 2.0 %w/v D-glucose was found to be the optimum concentration for maximum antibiotic production. High concentration of glucose is generally considered as repressor of secondary metabolisms [40] and maximum cell growth rates can inhibit antimicrobial agent production [41]. A catabolic repression of secondary metabolism produced by actinomycetes during actinomycin synthesis by Streptomyces antibioticus was reported after the addition of more glucose in the medium [42].…”
Section: Determination Of Optimum Concentration Of D-glucosementioning
confidence: 99%